Mindfulness on Stress of College Student - Virginia Maria Clarita Berek; Yeni Damayanti; Indra Yohanes Kiling (Journal of Health and Behavioral Science, 2020)
Stress occurs as a state under the pressure both physically and psychologically which blocks the individual’s and caused by the difference between what is expected to achieve and what is achieved. Individuals fail to achieve the goal because they cannot focus their attention directly and taking an action without awareness. The purpose of this study is to identify the effect of mindfulness on the stress of college students. This study hypothesizes that mindfulness has a negative effect on the stress of college students. The participants of this study were 400 college students of FKM Undana Kupang, aged 18-24 years old who were obtained by using simple random sampling. The analysis in this study used simple linear regression analysis. The results of this study indicate that the value (sig) = 0.000 < 0.05 and the value of t count > the value of t table i.e. as the amount of 5,644 > 2.249, means that there is a negative effect of mindfulness on college student’s stress, the increasing influence of mindfulness, the decreasing stress on college students.